Progress of Chinese and Western Medicine on Rotator Cuff Injury - Wang, Feiyu; Ni, Yuntao (Journal of Contemporary Medical Practice, 2025)
With the continuous development of medical technology, the average age of the population increases, people ‘s motor consciousness is generally improved, and the incidence of rotator cuff injury is increasing, which has become a common clinical soft tissue lesions around the shoulder joint, especially more common in elderly patients over 60 years of age. The pathogenesis of rotator cuff injury has not yet been conclusive in academia, and it belongs to the category of “shoulder pain” and “shoulder failure” in traditional Chinese medicine. Through consulting the relevant literature, to understand the etiology analysis and diagnosis and treatment of rotator cuff injury in Chinese and Western medicine were reviewed.